Clive Bell’s “Significant Form” and the neurobiology of aesthetics - Zeki, Semir (Frontiers in Human Neuroscience, 2013)
Though first published almost one century ago, and though its premise has been disputed, Clive Bell’s essay on aesthetics in his book Art still provides fertile ground for discussing problems in aesthetics, especially as they relate to neuroesthetics. In this essay, I begin with a brief account of Bell’s ideas on aesthetics, and describe how they focus on problems of importance to neuroesthetics. I also examine where his premise falls short, and where it provides significant insights, from a neuroesthetic and general neurobiological point of view.